Outcome of elderly patients with diffuse large B-cell lymphoma treated with R-CHOP: results from the UK NCRI R-CHOP14v21 trial with combined analysis of molecular characteristics with the DSHNHL RICOVER-60 trial. - Kuhnl, A.; Cunningham, D.; Counsell, N.; Hawkes, E. A.; Qian, W.; Smith, P.; Chadwick, N.; Lawrie, A.; Mouncey, P.; Jack, A.; Pocock, C.; Ardeshna, K. M.; et al. (Ann Oncol, 2017)
BACKGROUND: There is an on-going debate whether 2- or 3-weekly administration of R-CHOP is the preferred first-line treatment for elderly patients with diffuse large B-cell lymphoma (DLBCL). The UK NCRI R-CHOP14v21 randomized phase 3 trial did not demonstrate a difference in outcomes between R-CHOP-14 and R-CHOP-21 in newly diagnosed DLBCL patients aged 19-88 years, but data on elderly patients have not been reported in detail so far. Here, we provide a subgroup analysis of patients >/=60 years treated on the R-CHOP14v21 trial with extended follow-up. PATIENTS AND METHODS: Six hundred and four R-CHOP14v21 patients >/=60 years were included in this subgroup analysis, with a median follow-up of 77.7 months. To assess the impact of MYC rearrangements (MYC-R) and double-hit-lymphoma (DHL) on outcome in elderly patients, we performed a joint analysis of cases with available molecular data from the R-CHOP14v21 (N = 217) and RICOVER-60 (N = 204) trials. RESULTS: Elderly DLBCL patients received high dose intensities with median total doses of >/=98% for all agents. Toxicities were similar in both arms with the exception of more grade >/=3 neutropenia (P < 0.0001) and fewer grade >/=3 thrombocytopenia (P = 0.05) in R-CHOP-21 versus R-CHOP-14. The elderly patient population had a favorable 5-year overall survival (OS) of 69% (95% CI: 65-73). We did not identify any subgroup of patients that showed differential response to either regimen. In multivariable analysis including individual factors of the IPI, gender, bulk, B2M and albumin levels, only age and B2M were of independent prognostic significance for OS. Molecular analyses demonstrated a significant impact of MYC-R (HR = 1.96; 95% CI: 1.22-3.16; P = 0.01) and DHL (HR = 2.21; 95% CI: 1.18-4.11; P = 0.01) on OS in the combined trial cohorts, independent of other prognostic factors. CONCLUSIONS: Our data support equivalence of both R-CHOP application forms in elderly DLBCL patients. Elderly MYC-R and DHL patients have inferior prognosis and should be considered for alternative treatment approaches. TRIAL NUMBERS: ISCRTN 16017947 (R-CHOP14v21); NCT00052936 (RICOVER-60).
Keywords: Age Factors; Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/administration & dosage/adverse effects; Antineoplastic Combined Chemotherapy Protocols/*administration & dosage/adverse effects; Biomarkers, Tumor/*genetics; Cyclophosphamide/administration & dosage/adverse effects; Doxorubicin/administration & dosage/adverse effects; Drug Administration Schedule; Female; Gene Rearrangement; Humans; Kaplan-Meier Estimate; Lymphoma, Large B-Cell, Diffuse/*drug therapy/genetics/mortality/pathology; Male; Middle Aged; Multivariate Analysis; Patient Selection; Precision Medicine; Prednisone/administration & dosage/adverse effects; Proto-Oncogene Proteins c-bcl-2/*genetics; Proto-Oncogene Proteins c-bcl-6/*genetics; Proto-Oncogene Proteins c-myc/*genetics; Risk Factors; Rituximab; Time Factors; Treatment Outcome; United Kingdom; Vincristine/administration & dosage/adverse effects